(untitled) (Research, Society and Development, 2024)
Introduction: Charcot arthropathy is a degenerative and progressive disease that originates as a complication of peripheral neuropathy due to diabetes mellitus, causing joint deformities and serious consequences for diabetic patients. Objective: The aim of this study was to evaluate the clinical, epidemiological and pathophysiological aspects of the development of Charcot arthropathy in patients with diabetic neuropathy, building knowledge on the basis of case reports and knowledge based on the literature. Materials and Methods: This is an integrative literature review on the general clinical characteristics of the correlation between Charcot arthropathy and diabetic neuropathy. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Charcot Arthropathy”; “Diabetic Neuropathy”; “Interrelation” was cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: Most of the studies showed that Charcot arthropathy is a clinical condition that arises from the chronic evolution of diabetes mellitus, presenting a well-defined spectrum of clinical manifestations and requiring early intervention to avoid worsening the patient’s condition. Conclusion: Patients diagnosed with Charcot arthropathy should be managed as soon as possible to minimize the serious complications that accompany it, such as limb amputation. In addition, understanding that prevention, combined with patient education, is essential if the number of cases is to be reduced.